Effect of Microstructure on Corrosion of Steels in Aqueous Solutions Containing Carbon Dioxide - Al-Hassan, S.; Mishra, B.; Olson, D.L.; Salama, M.M. (Corrosion (Houston, Tex.), 1998)
INTRODUCTIONThe role of various environmental and metallurgical factors on corrosion of iron in carbon dioxide (CO2)bearing aqueous solutions has been the subject of several comprehensive reviews.1-2 DeWaard and Milliams3 suggested a mechanism where corrosion in this environment proceeds in a catalytic way by direct reduction of carbonic acid (H2CO3) and in which the charge-transfer reaction is the rate-determining step. Another study has shown that the corrosion rate increases with an increase in bicarbonate ion concentration.4-5 Several equations have been developed empirically to relate the corrosion rate to the partial pressure of CO2 (PCO2), temperature, and pH of the solution.6-9 These studies are helpful in the oil and natural gas industry in estimating corrosion behavior if the applied material properties and the environmental parameters are identical to those in the study. For an activation-controlled mechanism of corrosion, which is applicable below 60°C in a CO2saturated solution at atmospheric pressure, a corrosion rate equation has been developed for iron alloys using the fundamental reaction rate theory.10 Equation (1) is expressed in terms of only three process variables: pH, temperature, and PCO2:[Equation available in full paper]where k is the Boltzmann constant, T is the absolute temperature, and Q is the activation energy for the corrosion reaction. Equation (1) compares very well with most of the empirical relationships developed within a restricted range of T, pH, and PCO2 values.10 The equation allows the inclusion of other variables, such as flow, impurities, inhibitors, and steel microstructure through the